E-COMMERCE TRAINING FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) FOR HEALTH PRODUCT MARKETING - Abdul Aziz; Hartatik Hartatik; Naufal Wahyu (Yayasan Education and Social Center, 2023)
The presence of Micro, Small, and Medium Enterprises (MSMEs) in the Indonesian economy has a significant role and potential in building the national and sectoral economy. This community service aims to assist MSMEs in marketing their health products through e-commerce. E-commerce training is provided to provide an understanding of e-commerce platforms, marketing strategies, and effective product promotion techniques. In this training, participants will be given material on how to create an online store, determine product prices, and evaluate sales results. This training is expected to help MSMEs in increasing the sales of their health products and provide benefits to the community in need of health products